Effect of sowing and harvesting time on the growth and quality of lettice - Firoz, ZA; Rouf, MA; Mozumder, SN; Zaman, MM (Bangladesh Journal of Agricultural Research, 2008)
An experiment was conducted at the Hill Agricultural Research Station, Khagrachari from November 2002 to March 2003 to find out the effect of sowing time (10. 20, 30 November and 10, 20, and 20 December) and harvesting time (40, 50, 60, and 70 DAS) on the growth, yield, and quality of lettuce. Maximum yields were obtained from 10 November to 10 December sowing when harvested at 70 days after sowing (DAS) followed by 60 and 50 DAS. The lower yield was recorded from 20 and 30 December sowing when harvesting was done at 40 DAS. Though yield was maximum at 70 DAS, but quality of lettuce was not good, but harvesting at 50 DAS is suitable for quality lettuce production when sown between 10 November and 1 December. Key Words: Sowing dates, harvesting time, lettuce yield, lettuce quality. Bangladesh J. Agril. Res. 32(4) : 587-592.